2006
DOI: 10.1175/jas3702.1
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Planetary Waves before and after Stratospheric Sudden Warming Events in Several Phases of the Equatorial QBO

Abstract: Almost a thousand stratospheric sudden warming (SSW) events are obtained through long time integrations with a simple global circulation model, and a statistical analysis based on such a large number of samples is made to investigate behavior of planetary waves before and after SSW events depending on the phase of the equatorial quasi-biennial oscillation (QBO). An idealized zonal momentum forcing to mimic a phase of the QBO is imposed under a perpetual winter condition, and eight phases of the QBO-wind forcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 19 publications
4
37
2
Order By: Relevance
“…The HTE also holds when the QBO is defined by the vertical wind shear between 50 and 70 hPa, but it tends to be weaker for the QBO defined at other levels (Hitchman and Huesmann 2009, hereafter HH09). The HTE has been confirmed by observational studies (e.g., Dunkerton and Baldwin 1991;Naito and Hirota 1997;Lu et al 2008Lu et al , 2014 as well as by both mechanistic (e.g., O'Sullivan and Young 1992; Naito and Yoden 2006;Pascoe et al 2006) and complex general circulation models (e.g., Calvo et al 2009;Marshall and Scaife 2009). However, the mechanism behind the HTE is still under debate (e.g., Naoe and Shibata 2010;Yamashita et al 2011;Garfinkel et al 2012;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The HTE also holds when the QBO is defined by the vertical wind shear between 50 and 70 hPa, but it tends to be weaker for the QBO defined at other levels (Hitchman and Huesmann 2009, hereafter HH09). The HTE has been confirmed by observational studies (e.g., Dunkerton and Baldwin 1991;Naito and Hirota 1997;Lu et al 2008Lu et al , 2014 as well as by both mechanistic (e.g., O'Sullivan and Young 1992; Naito and Yoden 2006;Pascoe et al 2006) and complex general circulation models (e.g., Calvo et al 2009;Marshall and Scaife 2009). However, the mechanism behind the HTE is still under debate (e.g., Naoe and Shibata 2010;Yamashita et al 2011;Garfinkel et al 2012;Lu et al 2014).…”
Section: Introductionmentioning
confidence: 75%
“…In extreme cases, these wave disturbances can cause rapid breakdowns of the vortex and rising temperatures in the polar stratosphere, a phenomenon known as a stratospheric sudden warming (SSW; Labitzke 1982). It has been found that SSWs tend to occur more frequently under QBOe than under QBOw conditions (e.g., Dunkerton and Baldwin 1991;Naito and Hirota 1997;Lu et al 2008); thus, it is natural to suspect that a QBO modulation of planetary waves is responsible for the changes in the frequency of SSWs and the overall polar vortex strength (Holton and Tan 1980;Calvo et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labitzke (2004) even shows a statistical relation of SSW on the QBO and on the solar cycle, but the results for the SSW of 2009 did not fit with this statistical relation (Labitzke and Kunze, 2009) phase of the QBO while the other displaced SSWs lie on the easterly phase in the hight region between 25 and 50 km where the continuous westward wind band occurs (see http: //www.geo.fu-berlin.de/en/met/ag/strat/produkte/qbo). Naito and Yoden (2006) studied the PW activity before and after SSWs depending on the phase of the QBO by a numerical model. They found that the dominant zone of the upward and equatorward Eliassen-Palm flux in the lower stratosphere is shifted southward in the westerly phase and poleward in the easterly phase of the QBO during a SSW.…”
Section: Discussionmentioning
confidence: 99%
“…Arctic polar cap temperatures are significantly colder, and polar stratospheric heights significantly lower, when lower stratospheric QBO winds (e.g., winds near 50 hPa) are westerly than when they are easterly. Both modelingbased studies (e.g., Hampson and Haynes 2006;Pascoe et al 2006;Naito and Yoden 2006;Kinnersley and Tung 1999;Naoe and Shibata 2010;Calvo et al 2007;O'Sullivan and Young 1992, hereafter OY92;Niwano and Takahashi 1998) and reanalysis-based studies (e.g., Hu and Tung 2002;Hitchman and Huesmann 2009;Ruzmaikin et al 2005;Garfinkel and Hartmann 2007) have shown a robust effect of the QBO in the polar stratosphere. This effect is referred to as the Holton-Tan (HT) effect in the rest of this paper.…”
Section: Introductionmentioning
confidence: 99%